Necroptosis inhibitor directly reduced left ventricular dysfunction in obese-insulin resistant rats, independent of the metabolic status. (25th November 2020) - Apaijai, N; Jinawong, K; Singhanat, K; Jaiwongkam, T; Kerdphoo, S; Chattipakorn, S.C; Chattipakorn, N
Abstract: Background: The number of obese people is increasing globally. Our previous studies showed that chronic high-fat diet (HFD) consumption led to obesity with peripheral insulin resistance, which was associated with left ventricular (LV) dysfunction. Mechanistically, cardiac mitochondrial dysfunction and cell death are proposed as an underlying mechanism for LV dysfunction in obese subjects. Recently, necroptosis was defined as a novel cell death pathway, which can be found in various types of cardiac diseases such as myocardial ischaemia and heart failure. Pharmacological inhibition of necroptosis by necrostatin 1 (nec-1) provided the favorable outcomes to those cardiac diseases. However, the roles of necroptosis and the effects of nec-1 on the heart of obese-insulin resistant rats have never been investigated. Purpose: We hypothesized that nec-1 attenuates LV dysfunction by reducing cardiac mitochondrial dysfunction, necroptosis, and apoptosis in obese-insulin resistant rats. Methods: Male rats (n=32) were fed with normal diet (ND) or HFD for 12 weeks to induce obese-insulin resistance. At weeks 13, HFD-fed rats were assigned into 3 interventional groups (n=8/group) as follows: 1) HFD-fed rats treated with saline, 2) HFD-fed rats treated with nec-1 (1.65 mg/kg/day, subcutaneous injection), 3) HFD-fed rats treated with metformin (300 mg/kg/day, oral gavage feeding, served as a positive control). ND rats were treated with saline. Rats received their assigned interventions for additional 7 weeks. Blood pressure (BP), cardiac sympathovagal balance, and LV function were determined. At the end, the heart was excised to determine cardiac mitochondrial function including mitochondrial respiration, reactive oxygen species (ROS) levels, membrane potential changes, swelling, as well as apoptosis and necroptosis protein levels. Results: HFD-fed rats had increased body weight, visceral fat deposition, hyperinsulinemia with euglycemia, and dyslipidemia. Moreover, HFD-fed rats had increased systolic and diastolic BP, reduced cardiac sympathovagal balance, and %LV ejection fraction (LVEF) (Fig. 1A). For mitochondrial function, respiratory control ratio was decreased, ROS levels were increased, along with mitochondrial membrane depolarization and swelling (Fig. 1B). Both necroptosis and apoptosis were observed in HFD-fed rats. Treatment with nec-1 reduced systolic and diastolic BP, cardiac sympathovagal imbalance, and increased %LVEF (Fig. 1A). Necroptosis and apoptosis were reduced, and all mitochondrial function parameters were improved in nec-1 treated rats (Fig. 1B). However, the metabolic parameters were not modified by nec-1. Treatment with metformin had similar benefits as nec-1 (Fig. 1), with additional improvement in metabolic parameters in HFD-fed rats. Conclusion: Nec-1 directly improves LV function in obese-insulin resistant rats via attenuating cardiac mitochondrial dysfunction and cell death, independent of metabolic parameters. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Science and Technology Development Agency, Thailand Research Fund (TRF)